Associations Between Diagnosis with Type 2 Diabetes and Changes in Physical Activity among Middle-Aged and Older Adults in the United States. Issue 1 (20th February 2020) - Nicklett, Emily J; Chen, Jieling; Xiang, Xiaoling; Abrams, Leah R; Sonnega, Amanda J; Johnson, Kimson E; Cheng, Jianjia; Assari, Shervin
Abstract: Background and Objectives: Physical activity (PA) is an effective strategy for diabetes self-management and is central to the diabetes regimen. Diagnostic events present an opportunity for health behavior change; however, many older adults with type 2 diabetes (T2D) do not engage in regular PA. The relationships between diagnosis events and subsequent changes in PA are not well understood. Drawing upon life-course theory, this is the first study to examine whether the diagnosis of T2D is followed by a change in PA, whether these changes are sustained, and the sociodemographic characteristics associated with these changes. Research Design and Methods: We examined associations between T2D diagnosis and PA changes among 2, 394 adults ages 51+ from the Health and Retirement Study (2004–2014). PA changes were measured using metabolic equivalents of task (METs) estimated values accounting for the vigor and frequency of self-reported PA. Using piecewise mixed models, we examined initial and sustained changes in METs over time and tested whether these changes were modified by race/ethnicity, educational level, gender, and age at diagnosis. Results: Across participants, a significant postdiagnosis increase was observed in self-reported PA following the diagnostic event (β: 0.54, 95% CI: 0.10, 0.97). The steepness of decline in PA participation over time did not change significantly following T2D diagnosis. Age at diagnosis and race/ethnicity significantly moderated these relationships: participants diagnosed at older ages were less likely to improve PA following diagnosis and non-Hispanic whites experienced relatively steeper rates of decline following diagnosis with T2D. Discussion and Implications: Modest diagnosis-related increases in PA were observed among participants overall. The usual rate of decline in PA appears unaffected by diagnosis overall. Age at diagnosis and race/ethnicity moderated these relationships. Key implications for future research and clinical practice are discussed.